2016
DOI: 10.1038/srep33464
|View full text |Cite
|
Sign up to set email alerts
|

Protein malnutrition potentiates the amplifying pathway of insulin secretion in adult obese mice

Abstract: Pancreatic beta cell (β) dysfunction is an outcome of malnutrition. We assessed the role of the amplifying pathway (AMP PATH) in β cells in malnourished obese mice. C57Bl-6 mice were fed a control (C) or a low-protein diet (R). The groups were then fed a high-fat diet (CH and RH). AMP PATH contribution to insulin secretion was assessed upon incubating islets with diazoxide and KCl. CH and RH displayed increased glucose intolerance, insulin resistance and glucose-stimulated insulin secretion. Only RH showed a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In 2006 our research group observed the absence of amplifying pathways in islets from MSG‐obese rats, which was also found in the present study. However, previous study has demonstrated that insulin secretion induced by amplifying pathway is not altered in pancreatic islets from obese mice on a high‐fat diet . Thus, further studies will be necessary in order to better understand which mechanisms are underlying this difference between different animals model of obesity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2006 our research group observed the absence of amplifying pathways in islets from MSG‐obese rats, which was also found in the present study. However, previous study has demonstrated that insulin secretion induced by amplifying pathway is not altered in pancreatic islets from obese mice on a high‐fat diet . Thus, further studies will be necessary in order to better understand which mechanisms are underlying this difference between different animals model of obesity.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous study has demonstrated that insulin secretion induced by amplifying pathway is not altered in pancreatic islets from obese mice on a high-fat diet. 43 Thus, further studies will be necessary in order to better understand which mechanisms are underlying this difference between different animals model of obesity. Our data show that chronic exercise training reduces GSIS by inhibiting amplifying pathways in pancreatic islets; an effect that was more evident in islets from MSG-EXE rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, other mechanisms may be underlying the outcome induced by HFD on GSIS in protein‐restricted mice. In this sense, we have recently shown that the increment on GSIS in RH pancreatic islets is modulated by mitochondrial‐amplifying pathways of insulin secretion (51). Pancreatic islets from RH mice displayed lower mitochondrial membrane potential and increased ROS generation but without differences in ATP levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that diet-induced obesity, in mice, also provokes glucose intolerance accompanied by increased insulin secretion, which compensates for the peripheral insulin resistance [ 17 ]. This phenomenon has also been detected in metabolic programmed mice fed on a low-protein diet in early life followed by regular diet [ 2 ] or high-fat diet [ 5 , 18 ] during adulthood. Here, we confirmed these results with the LP + HF showing impaired insulin sensitivity and glucose tolerance, as well as an increased insulin secretion.…”
Section: Discussionmentioning
confidence: 87%
“…We have shown that mice fed on a low-protein diet in adolescence, followed by a high-fat diet during adulthood, develop glucose intolerance, insulin resistance, and reduced insulin secretion, compared to those fed on a high-fat diet during the whole experimental period [ 5 ]. This indicates that the metabolic programming, induced by malnutrition in early life, impairs insulin-glucose homeostasis to a greater extent than obesity per se.…”
Section: Introductionmentioning
confidence: 99%